Linking adverbials in research articles across eight disciplines - Matthew Peacock (Ibérica, 2010)
Biber et al. (1999) contend linking adverbials perform important cohesive and connective functions by signalling connections between units of discourse; however, there has been little previous corpus-based research in this important area of ESP. This paper describes an analysis of linking adverbials, such as “however” and “therefore”, in a corpus of 320 published research articles (RAs) across eight disciplines, four science and four non-science. New lists of linking adverbials were developed and the parameters of frequency, function and disciplinary variation were examined using WordSmith Tools. They were found to be more frequent than previously thought, with numerous statistically significant disciplinary differences, for example between the sciences and non-sciences. Also, they often clustered together in complex sequences. A close examination of RAs in two of the sciences revealed some reasons for the much lower rate of occurrence there. Authors developed claims in a different way, describing methods and results in a more narrative or descriptive style rather than explicitly telling readers the connections between ideas, claims and facts. Conclusions are that linking adverbials are more important in RAs as signalling and cohesive devices, and for helping RA authors construct and strengthen claims, than previously thought by experts in this field. Also, different disciplines achieve this in significantly different ways, confirming the importance of discipline variation when researching their use.